Implementasi Alat Hitung Sempoa sebagai Media Pembelajaran Matematika dalam Meningkatkan Kemampuan Numerasi Siswa Sekolah Dasar - Leni Nuraeni; Reza Muhamad Zaenal; Tio Heriyana (Jurnal Didactical Mathematics, 2025)
This study aims to determine the difference before and after applying abacus counting tool as a mathematics learning media in improving numeracy skills of elementary school students. The method used is quantitative with Pre-Experimental research type with The One Group Pretest-Posttest Design. This research will be conducted at SD Negeri Ciketak with the research subjects of class IV students totalling 18 students, using simple random sampling technique. The research instruments used were numeracy test sheets and non-test sheets (questionnaires) as student responses while the data analysis techniques used were descriptive and inferential statistics. Data analysis used prerequisite test, t-test of two dependent samples/paired samples t-test, wilcoxon test, N-Gain analysis and questionnaire data processing. The results showed that there was an average difference in students' numeracy skills by using abacus counting tools as a mathematics learning media. The N-Gain value with a mean of 0.6591 where the value is included in the medium category, meaning that there is a significant increase between the average numeracy skills of students using abacus calculator as a mathematics learning media. In addition, the questionnaire results showed positive responses from students. Thus, the implementation of abacus calculator as a mathematics learning media is effective in improving the numeracy skills of primary school students